Characterising the Subsurface Architecture and Stratigraphy of the McArthur Group through Integrated Airborne EM and Gravity Inversion. Issue 1 (1st December 2018) - Blaikie, Teagan; Soerensen, Camilla; Munday, Tim; Schaubs, Peter; Spinks, Sam; Schmid, Susanne; Kunzmann, Marcus
Abstract : The Caranbirini sediment-hosted Zn-Pb-Ag prospect is located west of the Emu Fault, 20 km north of McArthur River Mine (formally HYC), within the Batten Fault Zone of the McArthur Basin (Northern Territory). The Caranbirini area exposes stratigraphy from McArthur Group and shows some structural complexity with post-depositional folding and faulting. In order to better characterize the subsurface basin architecture we combine structural, sedimentological, and stratigraphic interpretations with 3D gravity inversion, and a 1D airborne electromagnetic inversion. Results are integrated to build a 3D model of the subsurface basin architecture, and identify prospective stratigraphy such as the Barney Creek Formation. 3D gravity inversions were performed using a preliminary 3D geological model of the project area as a reference model for a constrained property inversion. The gravity inversion identified an anomalous density zone immediately west of the Emu Fault. Interpretation of the inverted AEM data provided stratigraphic constraint for the geological model by defining the depth and geometry of the Barney Creek Formation. They also indicated the presence of several N-S trending faults to the west of the Emu Fault coincident with the western boundary of the anomalous density zone. The interpretation suggests that the depth to the Barney Creek Formation increases westwards of the Emu Fault. We interpret the increase in depth to the Barney Creek Formation, in combination with the zone of increased density as a fault-bounded sub-basin, bounded in the west by a paleo-high. Recognition of the sub-basin and controlling faults has implications for targeting Zn-Pb-Ag mineralization.